Pengembangan Media Ular Tangga Pembelajaran IPS Materi Negara Asean Untuk Kelas VI SD - Apriani, Frety Nur; Murjainah, Murjainah; Fuadiah, Nyiayu Fahriza (Indonesian Research Journal on Education, 2022)
The teacher's learning process has not used effective media, the learning process only usesthematic book sources and companion books and there are still some low learning outcomes insocial studies learning material for ASEAN countries students of class VI SDN 7 Muara Telang. Based on this, this study aims to produce social studies learning media material for ASEANcountries for class VI SD that is valid, practical, and effective. The type of research that is beingdeveloped is Research & Development (R&D) referring to the 4D model, namely definition,design, development, and dessiminate. In this study, the product was produced in the form of asnake and ladder media measuring 2 2 m with banner material. The data analysis technique wascarried out using percentage calculations which were then described to obtain valid, practical andeffective media results. Based on the results of data analysis using media validation, a percentageof 95.13% was obtained with very valid criteria and for material expert validation, a percentagevalue of 82.5% was obtained with very valid criteria. 66% with very practical criteria, in the small group results obtained 87.62% with very practical criteria, then through the field test from the pretest results obtained a percentage of 67.29% and 91.00% posttest can be seen from the group of criteria included in the 80 criteria %-100% with effectiveness category. So the results of thepretest and posttest test field tests get an increase of 23.71%. Thus, it can be concluded that themedia for social studies learning material from ASEAN countries can be said to be valid, practical, and effective.